Impelementasi Customer Relationship Management pada Sistem Informasi Pemasaran Toko Wibowo Motor - Ervyna Yulianingsih; Hani Atun Mumtahana; Ridho Pamungkas (LPPM Universitas Merdeka Madiun, 2021)
Wibowo Motor Shop is a trading unit engaged in the automotive sector, namely the sale of motorcycle spare parts and motorcycle accessories. The Wibowo Motor store in doing its marketing has not utilized information technology in order to increase customers. Toko Wibowo Motor wants to maintain good relations with customers by implementing a website-based Customer Relationship Management method. Customer Relationship Management is a strategy that is combined with the use of information technology in the form of software and computer hardware to assist companies in managing customer relationships. This marketing information system was built using the waterfall method. The result of the implementation of the marketing information system is that it can manage customer data, product data, promotions, product sales.